Remote linkage of record-breaking U.S. Tornado outbreaks to the tropical cyclone in western North Pacific in December 2021 - Jiang, Ning; Liu, Boqi; Zhu, Congwen; Chen, Yanying (Environmental research letters, 2023)
The frequency of tornadoes usually peaks during spring to summer rather than winter in climatology. However, the United States (U.S.) experienced more than 200 tornadoes in December 2021, which broke the historical record and caused 87 fatalities. Historically, the frequency of tornadoes in December tends to increase under El Niño conditions. Our results show that the monthly large-scale weather regime conducive to these record-breaking tornado outbreaks under a La Niña condition is closely associated with Typhoon Nyatoh in the western North Pacific. As the tropical cyclone (TC) recurved into the mid-latitudes, its interaction with the extratropical flows has caused distortions in the Asian jet stream and the dramatic development of anomalous anticyclone west of the dateline, which in turn strongly regulated the response of the monthly atmospheric teleconnection to La Niña forcing. Accurate forecasts of the monthly mean circulation for December 2021 first appeared in the European Center for Medium-Range Weather Forecasts sub-seasonal to seasonal forecasts from 29 November, with a forecast skill closely related to that of Typhoon Nyatoh. Given most studies on the warm seasons with frequent tornadoes, the present results advance our understanding of the TC effect on the monthly atmospheric response to El Niño-Southern Oscillation forcing and its linkage to the tornado occurrence during boreal winter.